Digital poetics in the classroom: the role of Taroko Gorge in increasing students’ engagement and critical thinking skills - Bannaga Taha Al-Zubair Hussen; Cut Irna Liyana; Nadifah (Asosiasi Relawan dan Pengelola Jurnal LPTNU (ARJUNU), 2025)
Background: The integration of generative e-poetry like Taroko Gorge into literary education addresses the growing need to bridge traditional and digital literacy in contemporary learning environments. Objective: This study aims to explore how Taroko Gorge enhances students’ engagement and critical thinking, and to identify the possible strategies for its integration into curricula. Method: Using a qualitative approach, this research combines observations, documentation, and interviews with 85 English Literature students at a university in East Java. Results: The findings of this study reveal that Taroko Gorge fosters high levels of engagement and analytical rigor while challenging students to adapt to dynamic textual interpretations. Effective integration strategies include interactive discussions and scaffolded analysis, which align with its generative nature. Implication: The implication is profound: generative e-poetry like Taroko Gorge not only revitalizes interest in literature but also prepares students to engage critically with evolving textual forms. Novelty: This study contributes to pedagogical innovation by positioning e-poetry as a transformative tool for modern literary education.